HOW EASTERNERS AND WESTERNERS UNDERSTAND THE WORLD AND HOW THIS UNDERSTANDING AFFECTS LANGUAGE (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This thesis posits that the epistemological and cultural frameworks of Easterners and Westerners fundamentally shape their understanding of the world, leading to distinct linguistic expressions and communicative styles. Eastern thought, often characterized by holism, interconnectedness, and contextuality, manifests in languages that emphasize relationships and ambiguity, while Western thought, rooted in individualism, analytical clarity, and linearity, promotes linguistic structures favoring precision and directness. This divergence in worldview not only influences vocabulary and grammar but also impacts conversational norms, ultimately reflecting deeper cognitive orientations and societal values that differentiate Eastern and Western modes of understanding and interaction.